2015
DOI: 10.4314/ahs.v14i4.21
|View full text |Cite
|
Sign up to set email alerts
|

Association between mean platelet volume levels and inflammation in SLE patients presented with arthritis

Abstract: Background: Systemic lupus erythematosus (SLE) may be characterized by periods of remissions and chronic or acute relapses. The complexity of clinical presentation of the SLE patients leads to incorrect evaluation of disease activity. Mean platelet volume (MPV) has been studied as a simple inflammatory marker in several diseases. There is no study in the literature about MPV levels in adult SLE patients with arthritis. Objectives: We aimed to investigate the MPV levels in the SLE population with arthritis duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 23 publications
8
59
1
1
Order By: Relevance
“…Furthermore, it was reported that MPV levels showed a positive correlation with disease activity and MPV levels decreased after psoriasis treatment [18]. In the study of Safak et al [28], MPV values of systemic lupus erythematosus patients in the active arthritis period were significantly lower than those of SLE patients in remission and a control group. On the other hand, the current study revealed that PDW levels were higher and MPV values were lower in the LP group compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that MPV levels showed a positive correlation with disease activity and MPV levels decreased after psoriasis treatment [18]. In the study of Safak et al [28], MPV values of systemic lupus erythematosus patients in the active arthritis period were significantly lower than those of SLE patients in remission and a control group. On the other hand, the current study revealed that PDW levels were higher and MPV values were lower in the LP group compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…One of these was excluded because they included other diseases [31]. Thus, nine articles met the inclusion criteria [3,[10][11][12][13][14][15][16][17] (Table 1, Figure 1). One report contained data on two different groups [12], so we analyzed these studies independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Studies on NLR, PLR, and MPV in SLE patients compared to healthy controls, on the relationship between NLR, PLR, and MPV levels and SLE activity, and on the association of NLR with renal involvement in SLE have reported controversial results [3,[10][11][12][13][14][15][16][17]. This may be because of the small sample sizes, low statistical power, and/or the presence of clinical heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be quite low in patients with SLE. 22 Keeping in China, Duan et al hypothesize that colon cancer might be originating from disputed bile acid homeostasis. 23 South African workers on the other hand 24 report dyslipidemia and anthropometric indicators among black/white adolescents.…”
mentioning
confidence: 99%